ANALISIS JENIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL FISIKA MATERI LISTRIK STATIS DI MAN 6 JOMBANG - Siti juwariyah; Trapsilo Prihandono; Sudarti Sudarti (JURNAL PEMBELAJARAN FISIKA, 2018)
AbstractThis research described students error and identify the cause of the students make mistakes in solving physics problems on static electrocity. Subjects in this study were 85 students of tweleveth grade on Islamic Senior High School 6 Jombang at 2017/2018 academic period. Interviews are conducted to eight students who became a representative of each error to determine the causes of students error. The results of students error identification on the subjects, among others; translation error amounted to 42,88% which indicates that percentage of translation error include medium error category, concept error amounted to 54,51% which indicates that percentage of concept error include medium error category, strategy error amounted to 15,88% which indicates that percentage of strategy error include low error category, and arithmetic error amounted to 1,76% which indicates that percentage of arithmetic error include very low error category. The cause of the error is identified, among others; students are not accustomed to write things that are known and asked questions, students do not know the purpose of the problem, students are accustomed to answer the question of physics without converting to SI units, students do not know the formula to be used, students are a hurry to do the work, and students are not careful when answered the questions.Key Words: arithmetic error, concept error, strategy error, translation error, static electrocity